Trauma induced testicular torsion: a reminder for the unwary - Seng, Y. J.; Moissinac, Kevin (BMJ Publishing Group, 2000)
Trauma induced testicular torsion is a well recognised entity, the incidence being 4–8% in most studies reporting on testicular torsion. The signs and symptoms of testicular torsion may easily be mistakenly attributed to preceeding testicular trauma if there was such an event. A patient is described with trauma induced testicular torsion who presented on three occasions before a decision was made to perform scrotal exploration. Unfortunately, an orchidectomy was the outcome. The message that trauma can and not infrequently does precipitate torsion, needs to be reiterated. Awareness of the entity and constant vigilance is required of clinicians to avoid a delay in definitive treatment.